Role of Diffusion Tensor Imaging in Functional Assessment of Transplant Kidneys at 3-Tesla MRI - Thambidurai S.; Venkatesh Kasi Arunachalam; Rupa R.; Sriman R. (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
Objectives The main purpose of this article is to measure the fractional anisotropy (FA) and apparent diffusion coefficient (ADC) values of cortex and medulla of renal allograft using 3-Tesla diffusion tensor imaging (DTI) in renal transplant patients with normal and graft dysfunction and to assess the correlation between diffusion tensor parameters (ADC and FA) and the estimated glomerular filtration rate (eGFR) value. Materials and Methods Fifty renal transplant recipients who received either living or cadaveric renal allografts were included in the study. Blood samples for serum creatinine and eGFR value were taken on the same day prior to the magnetic resonance study and the patients were assigned to three groups (A, B, C) according to allograft function (eGFR levels). The mean ADC and FA values of the cortex/medulla in upper, mid, and lower poles were calculated from the DTI sequence. Statistical analysis was performed using paired sample Student's t-test and one-way analysis of variance test. Results The mean ADC values of the cortex were higher than the medulla that was statistically significant. However, the mean FA values were significantly higher in the medulla than the cortex. Mean ADCs and FA of the renal cortex and medulla were significantly higher in group A patients with normal renal function than in group B and C with poor renal functions. The corticomedullary difference in the FA values was more in group A. However, this difference was lower in group B and more so in group C. Conclusion ADC and FA values in the renal cortex and medulla exhibit a good correlation with allograft function and were significantly lower in transplants with dysfunction than those with good function. FA values appear to be more sensitive than eGFR and ADC for detection of early pathological changes in the graft dysfunction.